2020
DOI: 10.1002/anie.202010458
|View full text |Cite
|
Sign up to set email alerts
|

Large Polyhedral Oligomeric Silsesquioxane Cages: The Isolation of Functionalized POSS with an Unprecedented Si18O27 Core

Abstract: The synthesis of organo‐functionalized polyhedral oligomeric silsesquioxanes (POSS, (R‐SiO1.5)n, Tn) is an area of significant activity. To date, T14 is the largest such cage synthesized and isolated as a single isomer. Herein, we report an unprecedented, single‐isomer styryl‐functionalized T18 POSS. Unambiguously identified among nine possible isomers by multinuclear solution NMR (1H, 13C, and 29Si), MALDI‐MS, FTIR, and computational studies, this is the largest single‐isomer functionalized Tn compound isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…We envision that materials with ultralow‐ k values (<1.5) are expected to be obtained when using T 14 , T 16 , and T 18 POSS as building blocks. [ 46,51 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We envision that materials with ultralow‐ k values (<1.5) are expected to be obtained when using T 14 , T 16 , and T 18 POSS as building blocks. [ 46,51 ]…”
Section: Resultsmentioning
confidence: 99%
“…In principle, larger POSS cages enable introduce more pores, which may be helpful for further reducing the k value of materials. High purity T 10 and T 12 POSS are usually difficult to be obtained from reliable commercial sources, [ 44–51 ] which raise the difficulties to investigate the effect of cage sizes over dielectric and other comprehensive properties of POSS‐based materials.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic protocol used to prepare styryl-functionalised Tn compounds (n=8, 10, 12 and 18) has been previously described in detail 30,31 . In the present study, and as previously found by Bassindale et al 22 , we found that changes in the work-up technique lead to a significantly different mixture of products, which are also obtained in higher yields than the fluoride-free Tn compounds obtained in our earlier studies.…”
Section: Synthesis Of Styryl-functionalised T8-fmentioning
confidence: 99%
“…We recently reported the synthesis and characterisation of a new family of styrylfunctionalised Tn POSS compounds (n=8, 10, 12 or 18), in which the styryl group was linked to the cage via the phenylene group rather than the vinyl group [30][31][32] . Such POSS compounds with organic moieties can be further modified via reactions such as hydrosilylation, Heck coupling, thiol-ene Click reactions, metathesis, etc, without modifying the structure of the Tn core.…”
Section: Introductionmentioning
confidence: 99%
“…A consequence of the difficulties encountered with post-functionalisation of the T8-F family has been limited progress in exploring potential applications for such compounds over the past two decades. In a previous study, we reported the synthesis of new styryl-based cage silsesquioxanes (Tn with n = 8, 10, 12 53 or 18 54 ), where the styryl group is bonded to all n vertices of the cages via the phenylene moiety. Subsequently, we described the preparation of the corresponding styryl-functionalised T8-F compound, 55 whose formation was facilitated by the presence of the electron-withdrawing group linked to the vertices of the T8 host.…”
Section: Introductionmentioning
confidence: 99%